Salafis’ Criticism on the Celebration of Prophet Muhammad’s Birthday - Muhammad As'ad (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2019)
This article explains the standing of the Salafis on the celebration of the Prophet Muhammad’s birthday or mawlid. It also captures some opinions of the proponents of the mawlid against the understanding of the Salafis. Generally, their criticism of this celebration is mainly built on their theological perspective due to three reasons. The first is the requirement of authenticity, as they argue that the mawlid has no argument or dalīl, either in the Qur’ān or in the ḥadīth. Another reason is the prohibition of innovation or bid‘ah due to the status of the mawlid as an innovative act, while the third is the reprehensibility of veneration and idolatry of the Prophet. However, the proponents of the mawlid reject these arguments, admit that it is inauthentic, falls under the category of good innovation or bid‘ah ḥasanah, and is allowed to be practiced. Additionally, the Salafis condemned some practices within the mawlid, such as serving food, the act of standing up or qiyām, the recitation of related books, and the use of musical instruments. Conversely, the proponents claimed that the practices were allowed as they did not violate any Islamic or sharī‘ah teachings. Also, they represent a sincere expression of joy and happiness for the birth of Allah’s messenger and noblest person, which is Prophet Muhammad.